Hits, flops, and other illusions ebook My fortysomething years in hollywood. - Zwick, Ed (2024)
A NEW YORK TIMES BESTSELLER * LOS ANGELES TIMES BESTSELLER * USA TODAY BESTSELLER " This funny, insightful, and deliciously dishy memoir" ( Town & Country ) from the director of Blood Diamond , The Last Samurai , Legends of the Fall , and Glory , creator of thirtysomething , and executive producer of My So-Called Life, " takes its place alongside Adventures in the Screen Trade and Easy Riders, Raging Bulls as one of the indispensable behind-the-scenes books for fans of movies and television" (Aaron Sorkin). "I'll be dropping a few names," Ed Zwick confesses in the introduction to his book. "Over the years I have worked with self-proclaimed masters-of-the-universe, unheralded geniuses, hacks, sociopaths, savants, and saints." He has encountered these Hollywood types during four decades of directing, producing, and writing projects that have collectively received eighteen Academy Award nominations (seven wins) and sixty-seven Emmy nominations (twenty-two wins). Though there are many factors behind such success, including luck and the contributions of his creative partner Marshall Herskovitz, he's known to have a special talent for bringing out the best in the people he's worked with, notably the actors. In those intense collaborations, he seeks to discover the small pieces of connective tissue, vulnerability, and fellowship that can help an actor realize their character in full. Talents whom he spotted early include Brad Pitt, Matt Damon, Denzel Washington, Claire Danes, and Jared Leto. Established stars he worked closely with include Leonardo DiCaprio, Anthony Hopkins, Tom Cruise, Julia Roberts, Anne Hathaway, Daniel Craig, Jake Gyllenhaal, Bruce Willis, Demi Moore, and Jennifer Connelly. He also sued Harvey Weinstein over the production of Shakespeare in Love —and won. He shares personal stories about all these people, and more. Written mostly with love, sometimes with rue, this memoir "is not just a wonderfully intimate memoir. It's also an indispensable guide to the shark-infested waters of artistic integrity" (Cameron Crowe). Destined to become a new Hollywood classic, Hits, Flops, and Other Illusions is "a must-read for any film fan, and a sacred text for any aspiring filmmakers out there" ( Forbes ).